Boosting mushroom production through innovative technologies - Shirur, Mahantesh; Sharma, V P (Indian Horticulture, 2019)
The mushroom component in a farming system augurs well to impart the diversification as it makes use of agro-residues of the farm and also recycle the spent mushroom compost after harvesting the mushrooms. Mushroom being an indoor crop, its farming is less affected by the vagaries of the climatic conditions. Mushroom can also be fitted either as an agribusiness with environment controlled production unit by the resource rich farmers or as a livelihood activity for small farmers. Many farmers in North Indian states have adopted mushroom cultivation as a regular farming activity during winter. The use of low cost mushroom houses made from bamboo, paddy straw and other cheap raw materials has made huge difference to their income levels. In recent times, the practice of adopting tropical mushrooms like Pleurotus sp. and Calocybe indica adjusting to the prevailing climate and using the same facilities has helped the farmers in getting round the year returns compared to just three to four months returns earlier. Extending the mushroom cultivation beyond winter has turned the mushroom growing as a year activity than as four months activity of growing white button mushroom alone in the past.